ACTN3 R577X and ACE I/D gene polymorphisms in Bulgarian athletes - Andonov, S.; Saraeva, R.; Andonova, S.; Kaneva, R.; Bachev, V.; Bonov, P.; Kremenski, I.; Atanasov, P. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Strength and speed human biomotor capacities are strongly genetically inherited, thus further influence with external stimuli (physical loading) when lack predisposition is almost impossible. The aim of this study was to analyse ACTN3 R577X and ACE I/D gene polymorphisms among 70 professional athletes, divided into three groups according to a power-time model, and 44 controls from Bulgarian population. Correlations have been made between genotypes and physiological and biochemical parameters at anaerobic conditions, using Wingate test. Genotyping was performed by RFLP analysis. We found that ACTN3 RR and RX genotypes significantly correlate with Peak Power Output (p=0,0004 and 0,004), Relative Power Output (p=0,0002 and 0,002) and Fatigue Index (p=0,04). Lactate Dehydrogenase enzyme activity was also statistically different in genotype before and after the Wingate test. In contrast, there were no significant differences when referred to XX genotype athletes and controls of those parameters. R-allele frequency was higher in Endurance group (0,70) than Anaerobic Capacity Group (0,50) (p=0,004), contrary to the prevailing data showing association of endurance with X-allele. ACE ID genotype athletes have significantly different PPO and RPO from ID controls, an observation which was not present in DD and II genotypes. We therefore conclude that XX genotype is unfavourable for speed/power performance. Higher R-allele frequency may lead to positive influence over the power component in endurance sports. Furthermore, the presence of D-allele in ACE heterozygous persons also indicates favourable conditions for speed and strength capacities development. References Alvarez R, Terrados N, et.al. Genetic variation in the renin-angiotensin system and athletic performance. Eur J Appl Physiol 2000 82(1-2) Druzhevskaya AM, Ahmetov II, Astratenkova IV, Rogozkin VA. Association of the ACTN3 R577X polymorphism with power athlete status in Russians. Eur J Appl Physiol 2008 103(6) MacArthur DG, North KN. Genes and human elite athletic performance. Hum Genet 2005 116(5) Montgomery HE, et al. The renin-angiotensin system and physical performance. Biochem Soc Trans. 2003 31(6) Nazarov IB, Woods DR, Montgomery HE, Shneider OV, Kazakov VI, Tomilin NV, Rogozkin VA The angiotensin converting enzyme I/D polymorphism in Russian athletes. Eur J Hum Genet 2001 9:797 801 Norman B. et al. Strength, Power, Fiber Types and mRNA expression in Trained Men and Women with different ACTN3 R577X Genotypes. J Appl Physiol. 2009 106(3) Roth SM, Hurley BF et al. The ACTN3 R577X nonsense allele is under-represented in elite-level strength athletes. Eur J Hum Genet 2008 16(3) Taylor RR, Mamotte CDS, Fallon K, van Bockxmeer FM. Elite athletes and the gene for angiotensin-converting enzyme. J Appl Physiol 1999 87(3) Woods D, et al.. Elite swimmers and the D allele of the ACE I/D polymorphism. Hum Genet 2001 108:230 232 Yang N., et al. ACTN3 genotype is associated with human elite athletic performance. Am J Hum Genet 2003 73(3)